Ar-implanted epitaxially grown HgCd Te: evaluation of structural damage by RBS and TEM - Aguirre, M. H. (2001)
Mercury cadmium telluride alloys Hg1-xCdxTe (MCT) is an important semiconductor material used in infrared photovoltaic detectors. Although ion implantation is a widely used technique in the manufacture of devices based on MCT, a detailed understanding of the n-type behaviour of the unannealed damage region has not yet been established. In the present paper n on p junctions were formed by Ar++ implantation on MCT(1 1 0) grown by isothermal vapour phase epitaxy method (ISOVPE). Comparison of the structural damage after implantation is evaluated by Rutherford backscattering spectrometry (RBS) and transmission electron microscopy (TEM) measurements for different doses. Damage distribution presents two peaks and defects are primarily vacancy dislocation loops in the first region. The observed n-type behaviour after implantation is attributed to the generation and diffusion of Hg from the damage region.